The “Ghosts” of IRAS Past and the Changing Cultural Context of Religion and Science - Peters, Karl E. (Zygon, 2015)
Beginning with our cosmic ancestors and the 1950s ancestors of Institute on Religion in an Age of Science (IRAS, the “Ghosts”), this essay highlights the wider, post-World War II cultural context, including other science and religion organizations, in which IRAS was formed. It then considers eight challenges from today's context. From the context of science there are (1) the challenge of scale that leads us to question our place in the scheme of things and can lead to a challenge to morale concerning whether we make any difference; (2) the challenge of human variability that leads to the question whether there is a single human moral nature; and (3) the challenge of detailed explanation that leads to the question of what is the task of theology in relation to detailed scientific explanation. From the religion context there are (4) the challenge of objectivity—studying religion without practicing religion; and (5) the challenge of pluralism and the variety of cultural and religious perspectives. From the context of the growing and diverse science-and-religion enterprise, considered from the perspective of IRAS developed in the first part of this essay, there are the challenges of (6) apologetics and (7) intellectualization. Finally, from the context of our growing, worldwide consumerist culture that is contributing to the radical alteration of the planetary environment, leading to much suffering, there is (8) the challenge of becoming more motivated to act for the long-term global good.